Characterization of electroless under bump metallury for AlSi bond pad composition - Norahmad Barzrul Basaruddin
The characterization of electroless under bump metallurgy for AlSi bond pad composition in term of surface morphology and surface roughness was investigated. By using the sample given, the gold layer need to be deposited on top on AlSi first. To deposit the gold layer, there are seven set-up process steps prior completion of under bump metallurgy (UBM) deposition, aluminum bond pad activation, first zincation, zinc removal, second zincation, electroless nickel and immersion gold. Then the completed sample needs to be analyzed. To obtain the surface roughness and morphology of each deposition, the Atomic Force Microscopy (AFM) and Scanning Electron Microscope (SEM) were used. The first zincation process has high surface roughness but preserved surface morphology of initial thin film surface. The second zincation provides the improved surface roughness due to the replacement aluminum layer with ion zinc in the solution.